2023
DOI: 10.3389/fenrg.2023.1245820
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of agricultural carbon emissions in China based on a GA-ELM model

Xiaoyang Guo,
Jingyi Yang,
Yang Shen
et al.

Abstract: Introduction: Strengthening the early warning of greenhouse gas emissions from agriculture is an important way to achieve Goal 13 of the Sustainable Development Goals. Agricultural carbon emissions are an important part of greenhouse gases, and accelerating the development of green and low-carbon agriculture is of great significance for China to achieve high-quality economic development and the goal of “carbon neutrality in peak carbon dioxide emissions”.Methods: By measuring the total agricultural carbon emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…The graph shows a decrease in CO 2 emissions over time, with a sharp decrease starting in 2022. The ELM model can only "learn" from the data it's trained on, and if the training data does not capture all the real-world factors influencing CO 2 emissions, the forecast may not perfectly reflect reality [ 5 ].
Fig.
…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The graph shows a decrease in CO 2 emissions over time, with a sharp decrease starting in 2022. The ELM model can only "learn" from the data it's trained on, and if the training data does not capture all the real-world factors influencing CO 2 emissions, the forecast may not perfectly reflect reality [ 5 ].
Fig.
…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…At the same time, with the continuous acceleration of urbanization, the carbon emissions between neighboring provinces are spatially dependent. In view of this, referring to the research results of China Physical Geography and Guo et al (2023), this paper divides the geographical region of China into eastern region, central region, western region and northeast region, so as to further investigate the differences in the impact of green finance on carbon emissions. Among them, each region contains provinces as shown in the table 8.…”
Section: Heterogeneity Test Of Sub-regionsmentioning
confidence: 99%
“…Qi et al used the PCA-GS-KNN model to predict agricultural carbon emissions in Zhejiang Province, China, and the results showed that the model can accurately predict regional agricultural carbon emissions 11 . Guo et al used the genetic algorithm optimisation and the extreme learning machine model to construct the Chinese agricultural carbon emissions prediction model to predict the peak trend of China's agricultural carbon emissions 12 .As interpretable machine learning has become increasingly popular, machine learning methods can extract unique insights from large datasets with a large number of feature variables [13][14] .Luo et al proposed a prediction model based on interpretable machine learning with Extra Tree Regression and SHAP to predict carbon emissions in the Yangtze River Delta region. The results showed that the overall areas of plowland, woodland, and grassland have a negative influence on carbon emissions, whereas the area of wave has an overall positive impact on carbon emissions 15 .…”
Section: Introductionmentioning
confidence: 99%